2018
DOI: 10.3747/co.25.4139
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Therapy for Breast Cancer in the Primary Care Setting

Abstract: ■ Hormone-positive bca is the most prevalent form of bca and, compared with the other subtypes, is usually associated with better survival.■ Survivorship has significantly increased for all stages of hormone-positive bca, making the primary care physician a key player in the care of affected patients.■ The two most common classes of anti-hormonal agents used in these patients are selective estrogen receptor modulators and aromatase inhibitors. Each class of medication is associated with signature side effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 46 publications
3
58
0
1
Order By: Relevance
“…The majority of invasive breast cancers are hormone receptorpositive (HR+) [1][2][3][4][5]. Endocrine therapy (ET), a key component of breast cancer treatment, reduces the risk of local and distant recurrence [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of invasive breast cancers are hormone receptorpositive (HR+) [1][2][3][4][5]. Endocrine therapy (ET), a key component of breast cancer treatment, reduces the risk of local and distant recurrence [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that patient non-adherence to adjuvant endocrine therapy is primarily caused by the adverse side effects on patients' quality of life (QOL) that are associated with such therapy [8,9]. These common side effects may include hot flashes, night sweats, fatigue, sleep disturbance, sexual dysfunction, joint stiffness, joint dysfunction and joint pain [9][10][11][12][13]. These symptoms may also negatively affect patients' functional ability.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for BC include surgery, chemotherapy, radiation therapy, endocrine therapy, and combination therapy. 2,4,5 Understanding the effects of estrogen and androgen on BC is critically important for treating BC. PC is the main male sex hormone-dependent cancer.…”
Section: Introductionmentioning
confidence: 99%